Perioperative practices in thyroid surgery: An international survey. Issue 7 (11th May 2017) - Maniakas, Anastasios; Christopoulos, Apostolos; Bissada, Eric; Guertin, Louis; Olivier, Marie‐Jo; Malaise, Jacques; Ayad, Tareck
Abstract: Background: Perioperative practices in thyroid surgery vary from one specialty, institution, or country to the next. We evaluated the preoperative, intraoperative, and postoperative practices of thyroid surgeons focusing on preoperative ultrasound, vocal cord evaluation, wound drains, and hospitalization duration, among others. Methods: A survey was sent to 7 different otolaryngology and endocrine/general surgery associations. Results: There were 965 respondents from 52 countries. Surgeon‐performed ultrasound is practiced by more than one third of respondents. Otolaryngologists perform preoperative and postoperative vocal cord evaluation more often than endocrine/general surgeons ( p < .001). Sixty percent of respondents either never place drains or place drains <50% of the time in thyroid lobectomies (43% for total thyroidectomies). Outpatient thyroid surgery is most frequently performed by surgeons in the United States (63%). Conclusion: This epidemiologic study is the first global thyroid survey of its kind and clearly demonstrates the variability and evolving trends in thyroid surgery. © 2017 Wiley Periodicals, Inc. Head Neck 39 : 1296–1305, 2017